A construção de um modelo multirreferencial para a coordenação de projetos coletivos em um Núcleo de Economia Solidária - Rufo, Carla Renata (Universidade Federal de São Carlos, 2018)
There is an apparent consensus that the economic and political transformations of neoliberalism have created an unstable social framework in Brazil since the 1990s, which aggravated impoverishment and social exclusion, allowing a new economy, based on the structuring of several associative forms of enterprise solidarity, gained more space as an alternative of resistance to this new cycle. The Technological Incubators of Popular Cooperatives (ITCPs) appear as a practice of university extension with the purpose of assisting these enterprises in their activities, acting as spaces for studies, research and development of social technologies aimed at the organization of work focused on self-management and playing an important role in the construction and collective resignification of knowledge. This thesis focuses on this theme by looking at the studies of science, technology and society (ECTS) with the aim of contributing to the dialogical construction of knowledge and knowledges aimed at the coordination of collective projects that are non-neutral and transdisciplinary in a Nucleus of Solidarity economy. Using an existential and integral action research, it was proposed the development of a spiral process that allowed the permanent reflection on the action with the actors truly involved in their emotional, sensorial, imaginative and rational integrality, for the development of a multireferential model on new practices for the coordination of projects in the Nucleus, the whole process being planned and conducted by a collective researcher, composed of people interested and willing to promote change. The hypothesis that guided the spiral process is that although the Core understood the importance of coordinating collective projects in a non-neutral and transdisciplinary way, how to do it still needed reflections to support it, which was in fact confirmed throughout the process. As evaluation of the process it was observed that there was good participation and collaboration of the members of the Nucleus; the formative aspects allowed to broaden the reflection of the participants on the theme and contributed in the construction of new knowledge on the coordination of collective projects not only conceived as ideal. The changes in the posture and everyday language of the participants also made it possible to note that not only was the debate established, but that conditions were created for it to remain. From the results of this action research, the strategic device developed for its conduct proved versatile to be applied in other contexts or with other questions; even if the multi-reference model built by the Nucleus is not generalized, it is possible that its elements serve as a starting point for further discussions in other spaces. It is hoped that reporting on the use of such a challenging research-action methodology will also contribute to other researchers in future directions.
The construction of a multireferential model for the coordination of collective projects in a Solidary Economy Nucleus
Keywords: Economia solidária; Ciência, Tecnologia e Sociedade; Tecnologia social; Complexidade; Transdisciplinaridade; CIENCIAS HUMANAS